Pricing of financial derivatives using PDEs - Chval, David; Kolman, Marek; Málek, Jiří, 1953-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This diploma thesis describes derivative pricing methods based on partial differential equations. The aim of this thesis is to show that methods based on partial differential equation can be a suitable alternative to the widely used Monte-Carlo method. First two chapters provide the theoretical background that is needed for grasping the whole topic. In the following parts is described finite difference method which is then applied to the Black-Sholes model and the Heston stochastic volatility model. In both cases is the finite difference method compared with Monte-Carlo method which is also described in this thesis.
Vedoucí práce: Marek Kolman
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses